Between the project and the everyday: The Guajuviras case - Mog, William (Revista Thésis, 2017)
Between the Guajuviras Housing Complex project designed due to a housing policy and the daily living of its residents due to the successive occupations and appropriations in time there is a his- tory full of con icts and tensions. This article aims to rescue this story emphasizing the contrasts within this housing produced and deployed in Canoas/RS between the 1970s and 1980s from the Companhia de Habitac?a?o (COHAB) site and the Banco Nacional da Habitac?a?o (BNH) and occupied illegally in 17 April 1987. This situ- ation was repeated in other cases in the Regia?o Metropolitana de Porto Alegre (RMPA) and is due to the clash between the strategic actions of those who conceived the project from a policy and tac- tics who shares the lives place everyday. This relationship is man- ifested in space perceived practices generating continuities and discontinuities that have an impact on the day-to-day lives. Today what is observed in “Guaju” as it is popularly known is a mosaic of di erent territories now approach and now turn away due to the daily dynamics developed by the locals.